Is there an asymmetric effect on monetary policy over time? A bayesian analysis using Austrian data - Sylvia Kaufmann (Oesterreichische Nationalbank (OeNB), 2001)
The present paper assesses whether monetary policy effects are asymmetric over the business cycle by estimating a univariate model for GDP including additionally the first difference of the 3-month Austrian interest rate as a measure for monetary policy. The asymmetry of the effects is captured by allowing for state-dependent parameters where the latent state variable follows a Marov switching process. The model is estimated within a Bayesian framework using Markov Chain Monte Carlo simulation methods. Model selection and specification tests are performed by means of marginal likelihood. The results document significant negative effects of monetary policy during periods of below-average growth, while the effect seems insignificant during periods of normal- or above-average growth. These results corroborate those derived in theoretical models assuming price rigidities and implying a convex supply curve. Additionally, the concern of using appropriate state-identifying restrictions is raised to obtain an unbiased posterior inference. Finally, the analysis concludes by assessing the robustness of the results w.r.t. alternative measures of monetary policy.
Keywords: 330; Asymmetry; monetary policy; Markov switching; Markov Chain Monte Carlo; marginal likelihood